2018
DOI: 10.1007/s11845-018-1758-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative treatment of appendicitis: public perception and decision-making

Abstract: Participant knowledge levels were variable with many concerned that non-operated appendicitis would always perforate. Perceptions of treatment were variable with some believing surgery was an absolute requirement and others preferring antibiotics due to the belief that NOTA is complication-free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…Expanding the results, in relation with the difference between the groups regarding complicated appendicitis, we found that length of surgery increased in COVID-19 times. Some studies did not show this difference [1,2]. Protection measures and usage of PPE can justify the results of our study regarding the time of surgery.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Expanding the results, in relation with the difference between the groups regarding complicated appendicitis, we found that length of surgery increased in COVID-19 times. Some studies did not show this difference [1,2]. Protection measures and usage of PPE can justify the results of our study regarding the time of surgery.…”
Section: Discussionsupporting
confidence: 47%
“…Acute appendicitis represents one of the most common emergency in a General Surgery Emergency Unit. The standard treatment for appendicitis is surgery, but some prefer using conservative therapy with good results in selected cases [1]. During the outbreak of COVID-19 pandemic, the incidence in abdominal emergencies declined.…”
Section: Introductionmentioning
confidence: 99%
“…Acute appendicitis is the most common acute surgical presentation [3]. While some groups and recent guidelines advocate conservative care [4,5] which is based on large cohort and randomized controlled trials that have suggested short‐term outcomes equivalent to surgery [6,7], in Ireland operative intervention had remained the predominant strategy before the pandemic [8]. Our surgical community held concerns over the seemingly high rates of failure with a conservative approach, and the risk of increasing overall hospital stay coupled with our lack in widespread availability of CT. We have examined how national practice preferences have changed over the last 6 weeks including analysis at patient experience level at our own institution, a major urban tertiary unit.…”
mentioning
confidence: 99%
“…Es wird nach den Prädiktoren für die Wirksamkeit der konservativen Therapie intensiv geforscht. Zusammenfassend imponieren der niedrige Wert von Alvarado-und AIR-Score, längere Symptomdauer vor der Aufnahme (>25 h), maximale Körpertemperatur von <37,3°C innerhalb 6 h nach Aufnahme und Appendixdurchmesser <11 mm (maximal 13 mm) als Prädiktoren für Erfolg, sowie Diabetes mellitus, intraluminale Flüssigkeit und Appendikolith als Risikofaktoren für Versagen der nichtoperativen Therapie einer AA [46][47][48][49][50][51].…”
Section: Explorative Laparoskopie Bei Akuter Appendizitisunclassified